Synergistic effect of La+Mo addition and optimum pH on the photocatalytic dye decomposition efficiency of spray pyrolyzed ZnO thin films. Issue 15 (1st August 2022) - Ravichandran, K.; Siva Jyothi, N.; Thirumurugan, K.; Chidhambaram, N.; Dineshbabu, N.; Shalini, R.; Praseetha, P.K.
Abstract: This work explores the photocatalytic degradation efficiency of lanthanum (La) and molybdenum (Mo) incorporated ZnO films deposited by nebulizer spray pyrolysis onto glass slides. The influence of La and (La + Mo) doping on certain physical properties was investigated. Photocatalytic behavior of the films was studied against methyl orange (MO) and methylene blue (MB) dyes. The impacts of dye adsorption, point of zero charge, and dye solution pH on the catalytic activity of ZnO:La:Mo films were probed and compared with those of their counterparts ZnO and ZnO:La thin films. The obtained results demonstrated that ZnO:La:Mo photocatalyst exhibited greater efficiency, reaching 98% and 85% degradation after 60 min for the cationic and anionic dyes, respectively for optimum pH. The degradation reactions follow the first-order kinetics and the rate of degradation increases by adding La and (La + Mo) to ZnO. The ZnO:La:Mo thin film exhibits excellent recyclability and stability even after five runs. A possible photocatalytic mechanism has also been proposed.